Embodied Resonances: The Sonic Pathways in Jean-Marc Vallée's film Wild. Issue 2 (September 2018) - Walker, Alison
Abstract : This paper seeks to translate the cinematic into the cinesomatic through a discussion of the embodied experience of cinema sound design. Cinesomatic is a neologism intended to articulate the perspective that any experience of film sound is inherently embodied, complex and generative. Building on the work of embodiment scholars such as Vivian Sobchack, Laura Marks and Jennifer Barker, among many others, who have applied philosophies of perception to audiovisual encounters, this paper is situated as a study of film soundtracks and audience experience written from the author's experience of Wild (Jean-Marc Vallée, 2014 ). As many studies of embodiment and film often examine senses other than hearing, there is a necessity within film sound scholarship to address this bias, and to integrate theories of body and the senses with discussions of specific film case studies. Following in the footsteps of these sensory theorists, and by drawing upon an embodied account of the filmic experience of the author as a case study, this paper aims to demonstrate how audiences' experience of films are 'lived' via the sound design. By paying close attention to the sonic elements of Wild that arguably provoke and engage the body, this paper aims to demonstrate ways in which sound consummates the lived experience of a cinematic narrative for a listener.